DIMER AND TRIMER CALIX[4]ARENES CONTAINING MULTIPLE METALLOCENE REDOX-ACTIVE CENTERS - SINGLE-CRYSTAL X-RAY STRUCTURE OF A BIS(FERROCENE)-BIS(P-TERT-BUTYLCALIX[4]-ARENE) HYDROPHOBIC HOST MOLECULE - Beer, P; Keefe, A; Slawin, A; Williams, D (1990)
The condensation of 1,1′-bis(chlorocarbonyl)ferrocene (1) and 1,1′-bis(chlorocarbonyl)ruthenocene (2) with p-t-butylcalix[4]arene gave the respective new redox-active metallocene-calix[4]arene dimers (3) and (4). An X-ray diffraction study of (3) shows the two calix[4]arenes to be in cone conformations with a metallocene metal atom transannular Fe⋯Fe separation of 5.9 Å. The reaction of 1,1′-bis(chlorocarbonyl)cobaltocenium chloride (5) and p-t-butylcalix[4]arene gave a cobaltocenium-bis(p-t-butylcalix[4]arene) dimer (6). A ferrocene-calix[4]arene trimer (7) was isolated from the reaction of (1) and calix[4]arene. Solution variable-temperature 1H n.m.r. studies show (3) and (4) to be conformationally mobile with respective low-temperature spectra consistent with either partial cone conformations or cis orientation of respective metallocene carbonyl ester moieties. Cyclic voltammetric and coulometric studies in acetonitrile reveal that compound (3) undergoes a reversible two-electron oxidation at +1.24V (versus saturated calomel electrode), suggesting the two respective ferrocene moieties are oxidised in one step. Proton n.m.r. complexation studies showed (3) to be incapable of forming a solution host-guest complex with t-butylamine.